Assessment of fecal coliform contamination on groundwater in Butuan City using remote sensing and geographic information system analysis - Japitana, Michelle V. (2010)
This study describes a method for the use of processed remotely-sensed data to infer ground-water flow directions and land cover data and the application of Remote Sensing (RS), Geographic Information System (GIS), and Multivariate Statistical Analysis (MSA) in assessing and characterizing the relationships among land cover, topographic features, well characteristics and other driving factors for fecal coliform contamination. In contrast to the conventional circular buffer zones used in various water quality studies, this research introduces the concept of pressure-gradient based capture zone (CapZone) to best characterize the potential contributing area (pca) to groundwater contamination. The study are covers Butuan City where majority of the population rely on groundwater as a source of potable drinking water. Urban growth in this city has resulted to rapid increase in population and demand for drinking water but efficient wastewater treatment facilities are sorely lacking. Though most of Butuan households are served by septic systems, these do not pass the standards imposed by the local government and numerous homes collect raw untreated sewage into pits. Thus, groundwater system in the study area becomes highly susceptible to fecal pollution. To determine the extent of fecal contamination, well water samples from 123 pump and dug wells were collected. A total of 90 CapZones were delineated based on analysis of topography and flow directions in the Shifted Digital Elevation Model (DEM), which was done in a GIS platform.For comparison, circular buffers of different radii were created at the same sampling points. To identify significant factors among wells sharing commonalities/dissimilarities of characteristics in each cluster, a data reduction tool called Hierarchical Analysis (HA) was employed. The HA resulted in 2 clusters for the pca employing the CapZone and buffer method. Derived regression models of FC density using the CapZone method generally yielded better R² values compared to the buffer method at three different radii. This suggests that the application of the CapZones as the pca can better characterize the influence of land cover and other causal factors to FC pollution compared to the buffer method. Furthermore, findings of this study showed that well characteristics such as depth, bottom elevation, age, and number of persons using the well; land use type like built - up and cropland; and slope are significant factors that can affect FC density. Thus, this study does not only prove the importance of employing RS-GIS techniques in assessing groundwater contamination but also offered a more physical plausible way of characterizing land cover influences on FC contamination to groundwater.
"October 2010"
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman
Keywords: Groundwater pollution -- Philippines -- Butuan City (Agusan del Sur); Enterobacteriaceae; Remote sensing -- Philippines -- Butuan City (Agusan del Sur)